Isolasi dan Identifikasi Bakteri Lipolitik dari Limbah Cair Kelapa Sawit (Elaeis quineensis Jacq.) - Khairani Khairani; Kartika Manalu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the ability of lipolytic bacteria to degrade lipids by obtaining isolates of lipolytic bacteria in palm oil industrial wastewater. By testing the ability of the lipolytic index, the research method used is a description method with bacterial isolation techniques using NA media (Nutrient Agar) and selective media for lipolytic agar. The results showed that there were 10 isolates of lipolytic bacteria with morphological and biochemical characteristics indicating three bacterial genera, namely, the genera Bacillus, Pseudomonas, and Klebsiella. Data analysis showed that 10 isolates of lipolytic bacteria had the potential to degrade lipids; the highest lipolytic activity index value of the isolates was found in isolate BL1 at 0.48 mm, and the lowest lipolytic index was found in isolate BL9 at 0.16 mm. In conclusion, isolating and identifying lipolytic bacteria in palm oil wastewater is one way to reduce environmental pollution that damages existing ecosystems in the environment. Keywords: Lipolytic Bacteria, Isolation, Palm Oil Effluent, Lipid